Mechanism of Oxidation of L-Histidine by Heptavalent Manganese in Alkaline Medium - Timy P. Jose; Sharanappa T. Nandibewoor; Suresh M. Tuwar (E-Journal of Chemistry)
The kinetics of oxidation of L-histidine by manganese(VII) in aqueous alkaline medium at a constant ionic strength of 0.05 mol dm-3 was studied spectrophotometrically. The reaction between permanganate and L-histidine in alkaline medium exhibits 2:1 stoichiometry (KMnO4: L-histidine). The reaction is of first order in [KMnO4], less than unit order in [L-histidine] and [alkali]. Decrease in the dielectric constant of the medium decreases the rate of reaction. Effect of added products and ionic strength of the reaction medium have been investigated. The main products were identified by spot test and I.R. A mechanism involving the free radical has been proposed. In composite equilibrium step L-histidine binds to MnO4- species to form a complex(C). The reaction constants involved in the different steps of mechanism are evaluated. The activation parameters with respect to slow step of the mechanism are computed and discussed and thermodynamic quantities are also determined.